2005
DOI: 10.1261/rna.2259406
|View full text |Cite
|
Sign up to set email alerts
|

A general two-step strategy to synthesize lariat RNAs

Abstract: We describe a general and efficient two-step strategy for lariat RNA synthesis. In the first step, a deoxyribozyme synthesizes 2¢,5¢-branched RNA. In the second step, T4 RNA ligase closes the loop that completes the lariat. The loop-closure reaction can form either a natural or unnatural lariat isomer, depending on which of the two 3¢-termini of the branched RNA reacts with the lone 5¢-end. We demonstrate two approaches to control formation of either lariat isomer. In conjunction with other routes for lariat R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…This will be of high significance for selective and internal nucleic acid labeling with multiple dyes on the same RNA, as for example requested by multicolor single-molecule FRET techniques 46 or for nucleic acid cyclization, 47 lariat formation or branching. 48 The possibility of reverse attachments will be of further interest in the emerging field of RNA nanotechnologies. 49 , 50 …”
Section: Resultsmentioning
confidence: 99%
“…This will be of high significance for selective and internal nucleic acid labeling with multiple dyes on the same RNA, as for example requested by multicolor single-molecule FRET techniques 46 or for nucleic acid cyclization, 47 lariat formation or branching. 48 The possibility of reverse attachments will be of further interest in the emerging field of RNA nanotechnologies. 49 , 50 …”
Section: Resultsmentioning
confidence: 99%
“…Independent of the chemical or enzymatic preparation of the linear precursor, the 5′-terminus needs to be phosphorylated to provide the functionality required for ligation. Phosphorylation can be performed chemically or enzymatically ( 71 ) followed directly by the circularization reaction ( 72 ) (Supplementary data, Protocols S3 and S4). In the case of enzymatically prepared RNA substrates, the 5′-terminal triphosphate resulting from the in vitro transcription reaction must be removed prior to phosphorylation by a polynucleotide kinase.…”
Section: Circularization In Vitromentioning
confidence: 99%
“…Separately, one of the deoxyribozymes found during development of the 8–17 selection pressure (6CE8)11 was shown to be useful for creating branched RNA with any branch-site nucleotide,16 which is one of the only nucleotides whose identity is restricted for 7S11. We also showed that another deoxyribozyme (6BX22) can be used for one-step synthesis of lariat RNAs directly related to biological sequences,17 and we developed a two-step ligation route to lariats that cannot be made efficiently in one step 18…”
Section: Rna Ligation With 5′-triphosphate Substratesmentioning
confidence: 99%